2019
DOI: 10.1093/pm/pnz176
|View full text |Cite
|
Sign up to set email alerts
|

Body Perception Disturbance and Pain Reduction in Longstanding Complex Regional Pain Syndrome Following a Multidisciplinary Rehabilitation Program

Abstract: Objective Clinical guidelines for the treatment of complex regional pain syndrome recommend multidisciplinary rehabilitation, yet limited evidence exists to support the effectiveness of this approach. Body perception disturbance, a common and debilitating feature of complex regional pain syndrome, is recommended by guidelines as important to treat. However, no study has yet explored whether disturbances change in response to multidisciplinary rehabilitation. We aimed to determine whether ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 31 publications
(63 reference statements)
0
13
0
Order By: Relevance
“…As symptoms of CRPS exhibit a variable progression over time, early initiation of therapy is integral to patient prognosis, with the goals of restoring limb functionality, decreasing pain, and improving quality of life [ 52 , 53 ]. This often requires a multidisciplinary approach involving patient education, physical and occupational therapy, psychiatry, and pain medicine specialists, along with pharmacological and surgical interventions.…”
Section: Current Treatmentmentioning
confidence: 99%
“…As symptoms of CRPS exhibit a variable progression over time, early initiation of therapy is integral to patient prognosis, with the goals of restoring limb functionality, decreasing pain, and improving quality of life [ 52 , 53 ]. This often requires a multidisciplinary approach involving patient education, physical and occupational therapy, psychiatry, and pain medicine specialists, along with pharmacological and surgical interventions.…”
Section: Current Treatmentmentioning
confidence: 99%
“…Although they must be considered within the limits of their low evidence value, case studies and preliminary investigations showed promising results of dedicated interventions (Stanton et al, 2018;Nishigami et al, 2019) addressing specific kind of SoP disorders at the baseline, as found in CRPS (Lewis et al, 2019).…”
Section: Treatment Studiesmentioning
confidence: 99%
“…Considering the complexity of the body experience phenomenon, future studies should consider the concomitant assessment of different domains of bodily experience (explicit and implicit SoP, BO, and SpP), in parallel to the clinical variables commonly used for clinical studies, as some authors have started to do with CRPS patients (Lewis et al, 2019). Intervention studies should determine the response of particular sub-groups of patients, for e.g., those with enlarged or diminished body perception Moreira et al, 2017;Adamczyk et al, 2018a), to dedicated perceptual training interventions (Lewis et al, 2019). Moreover, the preliminary detection of perceptual impairments and the potential identification of particular sub-groups in clinical studies may help to identify individuals who could potentially benefit from dedicated treatments, or sub-groups that may be resistant to usual cares.…”
Section: Recommendation For Future Researchmentioning
confidence: 99%
“…In terms of optimizing postoperative outcomes, our study suggests that the interest for rehabilitation becomes not only strengthening the joint and promoting full recovery to tasks, but also modifying a person's relationship with the new joint to achieve full incorporation or re-embodiment. Multidisciplinary rehabilitation programs for other conditions, including CRPS, include a range of strategies to increase re-embodiment and improve body perception disturbances (38). Enhanced or virtual reality interventions show promise in improving body perceptions, function, and proprioception in musculoskeletal conditions, including knee replacement (39)(40)(41).…”
Section: Discussionmentioning
confidence: 99%